The application and practice of chemistry in wearable devices for body fluid analysis - Nien, Hsin-Hua (2023)
Wearable devices improve personalize health care. The wearable devices can come in various convenient forms such as contact lenses, watch and skin patch to fit the clinical application. The wearable devices can be applied on different body fluid type including interstitial fluid, urine, tear, saliva, and sweat. Chemistry plays an important role on body fluid component analysis. Delicate design of chemistry response affects the analytic result display mode, detection accuracy and device stability. This article reviews the application and practice of chemistry in wearable device of body fluid analysis. Integration of chemistry and other detection systems provides many possibilities and opportunities on the development of future healthcare wearable devices. Keywords: Wearable device, glucose, lactate, healthcare